Electron microscopic analysis of partially replicated bacteriophage T7 DNA. - Burck, K B (1979)
Partially replicated bacteriophage T7 DNA was isolated from Escherichia coli infected with UV-irradiated T7 bacteriophage and was analyzed by electron microscopy. The analysis determined the distribution of eye forms and forks in the partially replicated molecules. Eye forms and forks in unit length molecules were aligned with respect to the left end of the T7 genome, and segments were scored for replication in each molecule. The resulting histogram showed that only the left 25 to 30% of the molecules was replicated. Several different origins of DNA replication were used to initiate replication in the UV-irradiated experiments in which 32P-labeled progeny DNA from UV-irradiated phage was annealed with ordered restriction fragments of T7 DNA (K. B. Burck and R. C. Miller, Jr., Proc. Natl. Acad. Sci. U.S.A. 75:6144--6148, 1978). Both analyses support partial-replica hypotheses (N. A. Barricelli and A. H. Doermann, Virology 13:460--476, 1961; Doermann et al., J. Cell. comp. Physiol. 45[Suppl.]:51--74, 1955) as an explanation for the distribution of marker rescue frequencies during cross-reactivation; i.e., replication proceeds in a bidirectional manner from an origin to a site of UV damage, and those regions of the genome which replicate most efficiently are rescued most efficiently by a coinfecting phage. In addition, photoreactivation studies support the hypothesis that thymine dimers are the major UV damage blocking cross-reactivation in the right end of the T7 genome.